Comparison of the Quality of Life and Work-Family Conflict between Veterans and Non-Veterans Workers - E. Talavari; A. Nisi (Afarand Scholarly Publishing Institute, 2015)
Aims: Neuro-psychiatric side effects caused by war lead to different problems affecting the veterans and their family members. Of main psychological aspects of the veterans, which are not often considered, are the quality of life, psychological health, and their conflict with job and family affairs. The aim of this study was to compare the quality of life and the work-family conflict between veterans and normal persons working at the southern oil sites. Instrument & Methods: In the causal-comparative study, 437 wokers of the southern oil sites, including 215 veterans and 222 normal persons, were studied in 2015. The veterans were selected via Relative Stratified Random Samling Method. The normal workers were selected considering their compliance with the veterans in job, age, and functions. Data were collected, using Quality of Life Questionnaire and Work-Family Conflict Questionnaire. Data was analyzed using one-variable ANOVA (in the MANOVA context) and Pearson Correlatio Coefficient. Findings: There was no significant difference in the mean scores of quality of life and work-family conflict between the veterans and the normal peoples (p>0.05). There was a powerful negative correlation between the quality of life and work-family conflict in veterans (r=-0.42) and normal peoples (r=-0.31), as well as in all the studied persons (r=-0.35; p<0.001). Conclusion: The quality of life and work-family confilict are approximately equal in the veterans and normal persons working at the southern oil sites. In addition, the persons are in a realtively good level of quality of life.